The Effect of Population Policy Features on the Change of Population Fertility Rate in 1970 – 2011 (Damascus University Journal of arts and humanities sciences, 2021)
Population growth rate in Syria reached (3.6%) in 1970, which is very high. This information evoked interest to the fact that if this high growth rate was to continue, it would create many population problems, and it would be an obstacle for economic and social development procedures .Population policy features in Syria began unofficially through family planning, maternal and child care, and other programs. In 1973 the government set up the National Population Commission. The Directorate of Human Planning was established in 1974, and the Syrian Family Planning Association was established. The commission took responsibility for an effective contribution in raising people’s awareness on the necessity of decreasing the population growth rate.The government later integrated population changes into the development plans. The government also took care of the population factor, which led to a decrease in the fertility rates in Syria.The study relied on many measures to study  the fertility level in Syria, and it showed that educating women leads to an increase in average marriage age and therefore a decrease in reproduction period of women.There is also an inverse correlation between the fertility level and urbanization as the increase in the percentage of urbanization leads to a decrease in fertility level.
Keywords: The Effect of Population Policy Features on the Change of Population Fertility Rate in 1970 – 2011